Ceruminous adenoma: an unusual mass in external auditory canal: a case report - Bhat, Manali; Vijayendra, H.; Vijayendra, Vinay Kumar; Mahajan, Nilesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Most masses in the external auditory canal (EAC) are either polyps or granulations secondary to an underlying inflammatory process. Less common swellings are exostosis and osteomas, a tumour being quite rare. A middle-aged female presented with a mass in the ear which mimicked a meningoencephalocele. However, further study revealed it to be a benign neoplasm of the ceruminous gland of the EAC-a ceruminous adenoma. The tumour was successfully excised with no recurrence on follow-up. A clinician must keep in mind the differential diagnosis of a mass in the EAC. A thorough examination and radiological investigations help aid in the diagnosis.